DA'WAH MANAGEMENT OF RELIGIOUS ACTIVITIES AT THE DARUL FALAH ISLAMIC BOARDING SCHOOL, AEK SONGSONGAN DISTRICT, ASAHAN REGENCY - Khairul Arifin; Ali Akbar (SOSIOEDUKASI, 2026)
Da'wah management is the process of managing religious preaching activities, encompassing planning, organizing, implementation, and evaluation to achieve da'wah objectives effectively and efficiently. This study aims to describe the implementation of da'wah management in religious activities at Darul Falah Islamic Boarding School, Aek Songsongan, Asahan Regency, and its role in improving the quality of religious development within the community. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation and were analyzed descriptively. The findings indicate that the implementation of da'wah management functions effectively supports various religious activities, including regular Islamic studies, majelis taklim, Islamic holiday commemorations, mosque youth development, and community-based da'wah programs. The success of these activities is supported by well-planned programs, clear task distribution, appropriate use of da'wah media, and continuous evaluation. Furthermore, the implementation of da'wah management enhances community participation, strengthens religious values, fosters noble character, and reinforces social relationships between the Islamic boarding school and the surrounding community. Therefore, da'wah management plays a vital role in creating well-organized, sustainable religious activities that have a positive impact on community life.